2023
DOI: 10.1101/2023.06.28.23291995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal multi-omics study reveals common etiology underlying association between plasma proteome and BMI trajectories in adolescent and young adult twins

Abstract: Background: The influence of genetics and environment on the association of the plasma proteome with body mass index (BMI) and changes in BMI remain underexplored, and the links to other omics in these associations remain to be investigated. We characterized protein-BMI trajectory associations in adolescents and adults and how these connect to other omics layers. Methods: Our study included two cohorts of longitudinally followed twins: FinnTwin12 (N=651) and the Netherlands Twin Register (NTR) (N=665). Follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Samples were first analyzed by independent data acquisition LC-MS/MS using a Q Exactive HF mass spectrometer and further analyzed using Spectronaut software. Data was locally normalized (Callister et al, 2006), and raw matrix counts were processed and quality controlled as described elsewhere (Drouard et al, 2023). Briefly, protein levels were log 2 -transformed and proteins with >10% missing values were excluded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were first analyzed by independent data acquisition LC-MS/MS using a Q Exactive HF mass spectrometer and further analyzed using Spectronaut software. Data was locally normalized (Callister et al, 2006), and raw matrix counts were processed and quality controlled as described elsewhere (Drouard et al, 2023). Briefly, protein levels were log 2 -transformed and proteins with >10% missing values were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the emergence of multi-omics studies in twin cohorts is challenged by high-dimensional designs. Multi-omics studies in twins are yet expected to improve our understanding of common traits (Hagenbeek et al, 2023), as was shown in few studies of mental health (Zhu et al, 2019), behavior (Hagenbeek et al, 2023), or body weight (Drouard et al, 2023; Bondia-Pons et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One twin study 9 has been conducted to quantify the heritability of blood proteins, but the sample size (36 MZ and 22 DZ twin pairs) and the number of proteins examined (N=342) were limited. Other twin studies have quanti ed protein heritability only for proteins associated with speci c traits 10,11 , but, to our knowledge, no twin study has quanti ed protein heritability across a large number of proteins in the proteome in moderate-to-large samples.…”
mentioning
confidence: 99%